Ferulic acid suppresses obesity and obesity-related metabolic syndromes in high fat diet-induced obese C57BL/6J mice - Weiwei Wang (Taylor & Francis Group, 2018)
This study aimed to determine whether mice fed ferulic acid (FA) would alleviate high-fat diet-induced obesity and obesity-related metabolic syndromes. Mice were divided into the following four groups and fed for 6 wk (n = 8): control diet (NC), high-fat diet (HF; 60% energy from fat), NC and HF supplemented with 0.5% (w/w) FA respectively. Mice fed HF-FA diet consumed same amount of energy, but had lower daily weight gain, white adipose tissue weight, body fat accumulation, blood glucose and had suppressed hepatic lipid accumulation and inflammatory cytokines (IL-6 and TNF-α) release (P < 0.05), compared with those in HF-fed mice. In conclusion, our findings indicate that dietary FA supplementation suppress body weight gain, body and hepatic fat accumulation, blood glucose elevation and inflammation in high fat diet-induced obese mice, suggesting that FA could be effective in lowering the risk of high fat-diet induced obesity and obesity-related metabolic syndromes.